Rare cause for a common presentation: isolated pulmonary valve endocarditis yet another mimicker. (18th July 2018) - Reza, Ahmed Shameem; Anand, Dharmesh; Cheng, Sing Huey; Anand, Dharampal
Abstract : Isolated pulmonary valve endocarditis (PVE) is a rare condition. Known risk factors in previous case reports were intravenous drug abuse and congenital heart disease. Epidemiology of PVE has been changing. It is now being reported specially following invasive healthcare-related procedures even in patients with structurally normal heart. Vast majority of patients present with respiratory symptoms and diagnosis of endocarditis may be challenging unless there is high index of suspicion. Various microorganisms had been isolated as aetiological agents; however, Enterococcus faecalis is being increasingly isolated. PVE mostly managed conservatively with intravenous antibiotics with option for surgical intervention in specific situations. We present a patient with isolated PVE due to E. faecalis following colonoscopy and polypectomy with predisposing risk factor of alcohol excess, mimicking clinically as pneumonia and radiologically as a neoplastic lesion.